The product rule is a fundamental concept in calculus that is essential to understanding and solving problems involving the products of two functions. In this article, we will explore the formula and applications of the product rule, providing examples to aid in comprehension.

In order to effectively utilize the product rule, it's important to remember the following formula:

**The derivative of the product of two functions (f*g) is equal to the first function (f) multiplied by the derivative of the second function (g), plus the second function (g) multiplied by the derivative of the first function (f).**

This formula can also be expressed using function notation as:

**The derivative of the product of two functions (f(x)g(x)) is equal to the first function (f(x)) multiplied by the derivative of the second function (g(x)), plus the second function (g(x)) multiplied by the derivative of the first function (f(x)).**

Where f and g are functions of x.

Let's take a look at some practical examples to further understand how the product rule works and how it can be applied.

- If f(x) = x^2 and g(x) = x^3, what is the derivative of (f*g)?
- We can start by breaking down the formula for the product rule and finding each part. In this case, f(x) = x^2 and g(x) = x^3, so:
**f(x) = x^2****g(x) = x^3**- Next, we can find the derivatives of f(x) and g(x):
**f'(x) = 2x****g'(x) = 3x^2**- Finally, we can substitute these values into the formula to find the derivative of the product:
**(x^2*x^3)' = (2x*x^3) + (x^2*3x^2)****= 2x^4 + 3x^4****= 5x^4**- If f(x) = sin(x) and g(x) = cos(x), what is the derivative of (f*g)?
- Similar to the previous example, we can start by finding each part of the formula:
**f(x) = sin(x)****g(x) = cos(x)**- Next, we can find the derivatives of f(x) and g(x):
**f'(x) = cos(x)****g'(x) = -sin(x)**- Using these values, we can plug them into the formula to find the derivative of the product:
**(sin(x)*cos(x))' = (cos(x)*cos(x)) + (sin(x)*(-sin(x)))****= cos^2(x) - sin^2(x)**- If f(x) = e^x and g(x) = x^3, what is the derivative of (f*g)?
- For this example, we can begin by breaking down the formula for the product rule and finding each part:
**f(x) = e^x****g(x) = x^3**- Next, we can find the derivatives of f(x) and g(x):
**f'(x) = e^x****g'(x) = 3x^2**- Finally, we can substitute these values into the formula to find the derivative of the product:
**(e^x*x^3)' = (e^x*3x^2) + (x^3*e^x)****= 3xe^x + x^3e^x**

for Free

14-day free trial. Cancel anytime.

Join **20,000+** learners worldwide.

The first 14 days are on us

96% of learners report x2 faster learning

Free hands-on onboarding & support

Cancel Anytime